A novel lncRNA PLK4 up‐regulated by talazoparib represses hepatocellular carcinoma progression by promoting YAP‐mediated cell senescence. Issue 9 (3rd April 2020) - Jia, Yan; Jin, Huanhuan; Gao, Liyuan; Yang, Xiang; Wang, Feixia; Ding, Hai; Chen, Anping; Tan, Shanzhong; Zhang, Feng; Shao, Jiangjuan; Wang, Shijun; Zheng, Shizhong
Abstract: A growing number of studies recognize that long non‐coding RNAs (lncRNAs) are essential to mediate multiple tumorigenic processes, including hepatic tumorigenesis. However, the pathological mechanism of lncRNA‐regulated liver cancer cell growth remains poorly understood. In this study, we identified a novel function lncRNA, named polo‐like kinase 4 associated lncRNA (lncRNA PLK4, GenBank Accession No. RP11‐50D9.3), whose expression was dramatically down‐regulated in hepatocellular carcinoma (HCC) tissues and cells. Interestingly, talazoparib, a novel and highly potent poly‐ADP‐ribose polymerase 1/2 (PARP1/2) inhibitor, could increase lncRNA PLK4 expression in HepG2 cells. Importantly, we showed that talazoparib‐induced lncRNA PLK4 could function as a tumour suppressor gene by Yes‐associated protein (YAP) inactivation and induction of cellular senescence to inhibit liver cancer cell viability and growth. In summary, our findings reveal the molecular mechanism of talazoparib‐induced anti‐tumor effect, and suggest a potential clinical use of talazoparib‐targeted lncRNA PLK4/YAP‐dependent cellular senescence for the treatment of HCC.